Effects of Different Stressors Are Modulated by Different Neurobiological Systems: The Role of GABA-A Versus CB1 Receptor Gene Variants in Anxiety and Depression - Gonda, Xenia; Petschner, Peter; Eszlari, Nora; Sutori, Sara; Gal, Zsofia; Koncz, Szabolcs; Anderson, Ian M.; Deakin, Bill; Juhasz, Gabriella; Bagdy, Gyorgy (Frontiers in Cellular Neuroscience, 2019)
Environmental stress and its interaction with genetic variation are key contributors in the development of depression and anxiety, yet there is a failure to identify replicable genetic variants and gene-interaction effects in the background of these psychiatric symptoms. Recently it has been reported that 5-HTTLPR and NOSI interact with financial but not other types of recent stressors in the development of depression. In the present study we investigated the interaction of GABRA6 rs3219151 and CNR1 rs7766029 in interaction with different types of recent life events on the presence of depression and anxiety in a large general population sample. 2191 participants completed the List of Threatening Experiences questionnaire which covers 4 categories of stressful life events (financial problems, illness/personal problems, intimate relationships, social network) experienced over the previous year and the Brief Symptom Inventory for depression and anxiety symptoms. Participants were genotyped for rs3219151 and rs7766029. Data were analysed with linear regression models with age and gender as covariates. Results indicated that CNR1 rs7766029 interacted significantly with financial but not other types of life events both in case of depression and anxiety symptoms. In contrast, GABRA6 rs3219151 showed a significant interaction with social network related life events in case of anxiety and with illness/personal problem-related life events in case of depression. Our results suggest that the psychological impact of different types of recent stress may be differentially modulated by distinct molecular genetic pathways. Furthermore, in case of certain genetic variants, the occurring psychiatric symptom may depend on the type of stress experienced.